PADI TUMBANG AT PAUD KANA" GROWTH SELF-MONITORING AT PAUD KANA AND PROVISION OF CATFISH NUGGETS TO PREVENT STUNTING IN PRESCHOOLERS - Aulya, Yenny; Lestari , Lilis; Setiawati, Erni; Mardiani, Diah Pipit; Rahmawati, Gita; Gustini, Hilda; Jubaeti, Deti; Nurfatin, Alifah (International Journal of Engagement and Empowerment (IJE2), 2025)
Toddlerhood is one of the critical phases for human growth and development. In the toddler period, a very rapid growth and development will affect the next life, and the continuity of growth and development of toddlers is affected by nutritional status. The nutritional status of toddlers is the nutritional condition of children aged 0-59 months determined by anthropometric methods, based on the index of Body Weight according to Age (BB / U), and Body Weight according to Height (BB / TB) (Izwardy, 2019).   This community service activity aims to exemplify to parents how to meet nutritional needs, one of which is by giving catfish nuggets, and how to "fall rice in paud kana" self-monitoring of growth and development in paud kana. This activity was carried out at PAUD Kana in West Bandung and involved children, parents, and school stakeholders. Patin fish nuggets are made from natural ingredients such as catfish, eggs, panir flour, pepper, onion, salt, and sugar, and are rich in protein to support children's health and growth. Nutrition education and demonstration on making fish nuggets were also provided to parents. The results of the activity showed that catfish nuggets not only attracted children, but also effectively increased their appetite. Through the nutrition education session and demonstration of making catfish nuggets, parents gained essential insights on providing healthy and nutritious food. This activity provides a practical solution to the problem of feeding difficulties in children and motivates families to adopt healthier eating habits. Catfish nuggets are an effective and easy-to-implement alternative to increase the appetite of toddlers, and support their optimal growth and development.